2005
DOI: 10.1159/000082542
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of RALGA, a Mixture of Retinaldehyde and Glycolic Acid

Abstract: Background: Retinoids and α-hydroxy acids (AHAs) are major compounds in topical therapy. They exert distinct but potentially complementary activities. However, their association is limited by their respective irritating potential. Recently, the first association between a retinoid and an AHA has been achieved; this formulation (RALGA) associates retinaldehyde (RAL) – a precursor of retinoic acid (RA) – and glycolic acid (GA) – an AHA. Objective: To study the pharmacological properties of RALGA. Methods: The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Second, glycolic acid, the other component of RALGA, is a peeling compound and is known to have a skin-depigmenting property in humans [15]. We have demonstrated that the presence of glycolic acid (6.4%) in a formulation containing 0.1% RAL significantly increases the bioavailability of RAL in the mouse skin [17]. Therefore, apart from its own depigmenting ability, glycolic acid could enhance the effect of RAL.…”
Section: Discussionmentioning
confidence: 99%
“…Second, glycolic acid, the other component of RALGA, is a peeling compound and is known to have a skin-depigmenting property in humans [15]. We have demonstrated that the presence of glycolic acid (6.4%) in a formulation containing 0.1% RAL significantly increases the bioavailability of RAL in the mouse skin [17]. Therefore, apart from its own depigmenting ability, glycolic acid could enhance the effect of RAL.…”
Section: Discussionmentioning
confidence: 99%
“…Topical RA and its 13-cis isomer (isotretinoin) are used as anti-acne therapeutic agents, whereas RAL is used in cosmetic formulations to slow down skin ageing or to lighten skin pigmentation [19][20][21]. On the other hand, most, if not all, depigmenting agents target tyrosinase, the enzyme that catalyzes the rate-limiting step of melanogenesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme activity of RALDH was assayed as described by Tran et al [34] , using a nonradioactive substrate for the enzyme. Thus, endogenous cytosol RA was subtracted from the cytosolic RA yield obtained after incubation with the enzyme substrates.…”
Section: Assay For the Enzyme Activity Of Raldhmentioning
confidence: 99%